2023
DOI: 10.3390/en16114470
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Scale-Up and Life Cycle Assessment for Wet Grinding Process of Pumice

Abstract: This study examines the grinding process of pumice based on the dry and wet laboratory measurements, scale-up method, and life cycle assessment. This research’s main goal was to set up the relation between scale-up and life cycle assessment results for the wet grinding process with the help of mathematical equations. Within the first research works, basic grinding testing in a laboratory dry Bond mill was accomplished. This step allowed the description of the estimated particle size distribution, median partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…We are aware that linking the methods used to measure sustainability with other disciplines (mathematics, statistics, and economics: T-set, T-Pareto optimality, and fuzzy) can provide more relevant and widely usable results [79][80][81][82]. In previous research studies [83,84] by the correspondence author, new mathematical equations have already appeared through LCA integrations. However, this research aimed to compare the scenarios of vegan, vegetarian, and meat-containing restaurant dishes regarding the entire life cycle of the products.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that linking the methods used to measure sustainability with other disciplines (mathematics, statistics, and economics: T-set, T-Pareto optimality, and fuzzy) can provide more relevant and widely usable results [79][80][81][82]. In previous research studies [83,84] by the correspondence author, new mathematical equations have already appeared through LCA integrations. However, this research aimed to compare the scenarios of vegan, vegetarian, and meat-containing restaurant dishes regarding the entire life cycle of the products.…”
Section: Discussionmentioning
confidence: 99%
“…Towards understanding the milling process, the effect of operating parameters on milling efficiency has been examined in recent years [24,25]. Other studies have reported that the breakage rate of particles varies significantly with the size distribution of the mill hold-up.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the impact of composting plants, it is essential to analyse their environmental impacts. LCA is one of the helpful methods for estimating potential environmental burdens and is mainly used for the construction industry (Buyle et al, 2013;Bahramian and Yetilmezsoy, 2020), grinding processes (Kruszelnicka, 2020;Mannheim and Kruszelnicka, 2022;Mannheim and Kruszelnicka, 2023); plastic manufacturing (Civancik-Uslu et al, 2018;Baldowska-Witos et al, 2019;Alhazmi et al, 2021;Mannheim, 2021), and waste management (Brancoli and Bolton, 2019;Alwaeli and Mannheim, 2022;Cano-Londoño et al, 2022;Rimantho et al, 2022;Avató and Mannheim, 2022;Mannheim, 2022). In the last decade, the environmental impacts associated with livestock and crop production have become increasingly significant.…”
Section: Introductionmentioning
confidence: 99%